Marked Seizure Reduction after MCT Supplementation - Raed Azzam; Nabil J. Azar (Case Reports in Neurological Medicine)
We report the case of a 43-year-old man with history of nonsurgical partial epilepsy who previously failed multiple trials of antiepileptic drugs. Medium-chain triglycerides (MCT) were added to his regular diet in the form of pure oil. Subsequently, his seizure frequency was markedly reduced from multiple daily seizures to one seizure every four days. His seizures recurred after transient discontinuation of MCT over a period of ten days. His seizure improvement was achieved at a dose of four tablespoons of MCT twice daily with no reported side effects. He developed significant diarrhea and flatulence at higher doses. We conclude that MCT oil supplementation to regular diet may provide better seizure control in some patients. MCT oil supplementation may be a more tolerable alternative to the standard ketogenic diet.